The design and preparation of specification for air conditioning system for the School of Hotel and Catering ITM, Shah Alam / Najib Hashim and Azhar Mohammad - Hashim, Najib; Mohammad, Azhar (1991)
This final year project report has been compiled with, the primary aim of describing on the project that we had done for the period of three semester as a part of fulfilment for the award of Advanced Diploma In Mechanical Engineering. The main objective of this project is to Design and Prepare the Specification of Air-conditioning System for the School of Hotel and Catering,ITM, Shah Alam. Basically there are two main blocks at the Hotel and Catering building: Block A -Academic block consist of two levels. It includes the Lecture theatre, Instructor room, Administration office, Computer Library, Lecturer's room etc.